Mathematics with applications : in the management, natural, and social sciences / Margaret L Lial, Thomas W Hungerford - Lial, Margaret L.
Best known for realistic and varied applications, an abundance of helpful pedagogy, and solid algebra review, the new edition of this text offers updated and new applications, and increased optional graphing technology.